2001
DOI: 10.1007/s004100000218
|View full text |Cite
|
Sign up to set email alerts
|

Multiple zircon growth during fast exhumation of diamondiferous, deeply subducted continental crust (Kokchetav Massif, Kazakhstan)

Abstract: Diamondiferous rocks from the Kokchetav Massif, Kazakhstan, represent deeply subducted continental crust. In order to constrain the age of ultra high pressure (UHP) metamorphism and subsequent retrogression during exhumation, zircons from diamondiferous gneisses and metacarbonates have been investigated by a combined petrological and isotopic study. Four dierent zircon domains were distinguished on the basis of transmitted light microscopy, cathodoluminescence, trace element contents and mineral inclusions. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
143
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 415 publications
(156 citation statements)
references
References 40 publications
9
143
0
4
Order By: Relevance
“…Garnet in these gneisses displays a large unzoned core and narrow rims with decreasing Ca and increasing Mg contents [28,29]. Similar zoning has been observed in some dolomitic metacarbonates [20]. It was suggested that the observed garnet zoning reflects decompression [20] from UHP to granulite-facies conditions.…”
Section: Geological Background and Sample Descriptionmentioning
confidence: 66%
See 2 more Smart Citations
“…Garnet in these gneisses displays a large unzoned core and narrow rims with decreasing Ca and increasing Mg contents [28,29]. Similar zoning has been observed in some dolomitic metacarbonates [20]. It was suggested that the observed garnet zoning reflects decompression [20] from UHP to granulite-facies conditions.…”
Section: Geological Background and Sample Descriptionmentioning
confidence: 66%
“…The peak metamorphic temperature is constrained at 950-1000 • C [17][18][19][20]. A minimum pressure of 4.3 GPa is given by the presence of diamond and the maximum pressure of about 6.0 GPa is defined by the stability of dolomite [21,22].…”
Section: Geological Background and Sample Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). They have homogeneous cores whereas slight variations in their composition occur in narrow ($100 mm) external zones (Shatsky et al, 1995;Korsakov et al, 1998;Hermann et al, 2001;Korsakov et al, 2002;Korsakov & Hermann, 2006). Diamond and coesite inclusions identified in the garnet porphyroblasts point to peak metamorphic conditions of P$4-6 GPa and T$950-1000 C (Sobolev & Shatsky, 1990;Hermann et al, 2001;Korsakov et al, 2007).…”
Section: Sample B01-3mentioning
confidence: 99%
“…BSE images of garnet porphyroblasts and P-T paths for coesite-(a-d) and diamond-grade (e-f) metamorphic rocks from the Kokchetav massif plotted on metamorphic facies diagram (after Liou et al, 1998;Okamoto & Maruyama, 1999). The P-T stages indicated along the path of the coesite-and diamond-grade metamorphic rocks are based on petrologic data of Parkinson (2000), Theunissen et al (2007) and Hermann et al (2001), Korsakov et al (2007), respectively. Thick arrows indicate the different stages of garnet growth.…”
mentioning
confidence: 99%